Marine algae sulfated polysaccharides for tissue engineering and drug delivery approaches - Silva, Tiago H. (2012)
Biomedical field is constantly requesting for new biomaterials, with innovative properties. Natural polymers appear as materials of election for this goal due to their biocompatibility and biodegradability. In particular, materials found in marine environment are of great interest since the chemical and biological diversity found in this environment is almost uncountable and continuously growing with the research in deeper waters. Moreover, there is also a slower risk of these materials to pose illnesses to humans. In particular, sulfated polysaccharides can be found in marine environment, in different algae species. These polysaccharides don’t have equivalent in the terrestrial plants and resembles the chemical and biological properties of mammalian glycosaminoglycans. In this perspective, are receiving growing interest for application on health-related fields. On this review, we will focus on the biomedical applications of marine algae sulfated polymers, in particular on the development of innovative systems for tissue engineering and drug delivery approaches.